EUPHONY IN THE UNDERSTANDING OF IVAN FRANKО - Kasіanova, O.; Касьянова, О. (Київський національний університет імені Тараса Шевченка, 2022)
Much has been written about Ivan Franko's creative heritage as a multi-volume, innovative, multi-genre and diverse style. Instead, the Franco-scientist is still little known. In our article we will consider only a "drop" of Ivan Franko's scientific work – the sound organization of a poetic work, which is part of Franko's works on the structure and functioning of a literary work. This aspect of his work was studied by F. Pustova, A. Voytiuk, R. Gromyak, M. Hnatyuk, L. Nevidomska, O. Nastenko and others. These scholars outlined Franko's theory of the influence of text on the reader, outlined the criteria of poetic thought on the melodiousness and functioning of the means of recording poetic works, considered the aesthetic concept of the scientist in terms of communication, the essence of poetry, its linguistic foundations and more. Note that the linguistic foundations of the sound organization of Ivan Franko's poetic text are still insufficiently covered, so in this article we consider the concept of melodiousness in the understanding of Ivan Franko, compare it with the modern interpretation of euphony. In his interpretation of melodiousness, Ivan Franko demonstrates an interdisciplinary approach to the definition of the phenomenon, because he is not afraid to go beyond literary studies and move into the plane of linguistics, and sometimes even translation studies. Frank's understanding of the sound organization of a poetic work is based on the perception of speech as the basis of the subjective impression of language in general, which by its characteristic sound forms in the listener a certain sound image of it. That is, melodiousness, according to Frank, is not limited to the ratio of vowels and consonants. His interpretations of the sound organization of the poetic text are not inferior to the current study of euphony. Euphony in Ivan Franko's understanding is a harmonious unity of content and form, which the scientist not only analyzed but also tried to embody in his poetic work, the study of which is no less relevant today in terms of linguistic principles and the scientist's thoughts on the organization of poetic text.

Розглянуто напрацювання І. Франка про звукову організацію поетичної мови. Проаналізовано поняття милозвучності в розумінні І. Франка, порівняно його з сучасним трактуванням евфонії.
МИЛОЗВУЧНІСТЬ У РОЗУМІННІ ІВАНА ФРАНКА
Keywords: phonics; melodiousness; melody; euphony; vowel; consonant; sound; assonance; assonance; alliteration; фоніка; милозвучність; мелодійність; евфонія; голосний; приголосний; звук; асонанс; асонанція; алітерація